8-Week Supplementation of 2S-Hesperidin Modulates Antioxidant and Inflammatory Status after Exercise until Exhaustion in Amateur Cyclists - Francisco Javier Martínez-Noguera; Cristian Marín-Pagán; Jorge Carlos-Vivas; Pedro E. Alcaraz (MDPI AG, 2021)
Both acute and chronic ingestion of 2S-hesperidin have shown antioxidant and anti-inflammatory effects in animal studies, but so far, no one has studied this effect of chronic ingestion in humans. The main objective was to evaluate whether an 8-week intake of 2S-hesperidin had the ability to modulate antioxidant-oxidant and inflammatory status in amateur cyclists. A parallel, randomized, double-blind, placebo-controlled trial study was carried out with two groups (500 mg/d 2S-hesperidin; n = 20 and 500 mg/d placebo; n = 20). An incremental test was performed to determine the working zones in a rectangular test, which was used to analyze for changes in antioxidant and inflammatory biomarkers. After 2S-hesperidin ingestion, we found in the rectangular test: (1) an increase in superoxide dismutase (SOD) after the exercise phase until exhaustion (p = 0.045) and the acute recovery phase (p = 0.004), (2) a decrease in the area under the oxidized glutathione curve (GSSG) (p = 0.016), and (3) a decrease in monocyte chemoattractant protein 1 (MCP1) after the acute recovery phase (p = 0.004), post-intervention. Chronic 2S-hesperidin supplementation increased endogenous antioxidant capacity (↑SOD) after maximal effort and decreased oxidative stress (↓AUC-GSSG) during the rectangular test, decreasing inflammation (↓MCP1) after the acute recovery phase.